Terrible Silent danger of Pelvic Inflammatory Disease: Nurse roles: บทบาทพยาบาล - Phuthasane, Chatchadaporn; Punthasee, Pornsiri (Journal of Health Sciences and Wellness, 2021)
Pelvic inflammatory disease resulted from infection of the lower genital area into the pelvic organs. There are causes and risk factors derived from inappropriate sexual behavior, sexual infections, hormonal changes and non-sterile procedures which affect complications and the quality of life of patients such as tubo-ovarain abscess, pelvic fascia, ectopic pregnancy or infertility. Even if the diagnosis and treatment are currently much more effective and receive rapid screening but there are some patients do not show symptoms in the early phase. These patients will undergo surgery urgently because are serious complications and life-threatening such as an infection into the blood stream, rupture of abscess in the fallopian tubes or ovaries and bleeding in the pelvic cavity leading to shock and death. Therefore, nurse is importance health personnel for preventing PID and its recurrence in women by providing health education regarding avoid causes and risk factors of PID and self-care of PID. If there are abnormal symptoms, should see a doctor soon for appropriate treatment immediately.